EDUCATION AS A COMMODITY: A STUDY OF POSITION OF HIGHER EDUCATION IN SRI LANKAN VALUE SYSTEM - Christy, Antonet Lucksicca; Rajapakshe, Kamalpitiya Rajapakshelage Thilakshi Samilka Sandaruni (PEOPLE: International Journal of Social Sciences, 2018)
Higher education is considered as one of the most important empowerment tool in Sri Lankan value system since it is believed to have a direct link with financial status, social standards and self-development. Considering that it plays an important role in Sri Lankan value system, this paper aims to find out the level of importance given to higher education among different classes, genders and ethnic groups in Sri Lanka. As means to explore this area, method of survey with questionnaires and interviews has been used with a random sample of 100 people. As a result of this study, it was found that citizens of Sri Lanka who belongs to working class lacks the information and the interest for higher education for all the genders, the citizens of middle class are determined to pursue masters level and doctoral level of education and the upper class citizens are determined to follow only until bachelors’ level of education. Hence the findings can be summarized that higher education is not much valued in working class where as it plays a main role in middle class whilst it is only valued as a secondary goal next to money and status in upper class value system.